Diet-induced obesity leads to metabolic dysregulation in offspring via endoplasmic reticulum stress in a sex-specific manner - Park, J H; Yoo, Y; Cho, M; Lim, J; Lindroth, A M; Park, Y J (International Journal of Obesity, 2018)
Background/Objectives: Exposure to metabolic stress has been suggested to influence the susceptibility to metabolic disorders in offspring according to epidemiological and animal studies. Nevertheless, molecular mechanisms remain unclear. We investigated impacts of diet-induced paternal obesity on metabolic phenotypes in offspring and its underlying molecular mechanism. Subjects/Methods: Male founder mice (F0), fed with control diet (CD) or high-fat diet (HFD), were mated with CD-fed females. F1 progenies were mated with outbred mice to generate F2 mice. All offspring were maintained on CD. Metabolic phenotypes, metabolism-related gene expression and endoplasmic reticulum (ER) stress markers were measured in serum or relevant tissues of F2 mice. DNA methylation in sperm and testis of the founder and in the liver of F2 mice was investigated. Results: Male founder obesity, instigated by HFD, led to glucose dysregulation transmitted down to F2. We found that F2 males to HFD founders were overweight and had a high fasting glucose relative to F2 to CD founders. F2 females to HFD founders, in contrast, had a reduced bodyweight relative to F2 to CD founders and exhibited an early onset of impaired glucose homeostasis. The sex-specific difference was associated with distinct transcriptional patterns in metabolism-related organs, showing altered hepatic glycolysis and decreased adipose Glucose transporter 4 (Glut4) in males and increased gluconeogenesis and lipid synthesis in females. Furthermore, the changes in females were linked to hepatic ER stress, leading to suppressed insulin signaling and non-obese hyperglycemic phenotypes. DNA methylation analysis revealed that the Nr1h3 locus was sensitive to HFD at founder germ cells and the alteration was also detected in the liver of F2 female. Conclusion: Our findings demonstrate that male founder obesity influences impaired glucose regulation in F2 progeny possibly via ER stress in a sex-specific manner and it is, in part, contributed by altered DNA methylation at the Nr1h3 locus.